„Imię Twoje […] im bardziej puste, tym bliższe prawdy”. O nie-nazywaniu Boga w poezji Zbigniewa Jankowskiego - Rybka, Małgorzata; Sławek, Jolanta (Poznańskie Spotkania Językoznawcze, 2014)
The linguistic image of God in the poetry of Zbigniew Jankowski is not homogenous. God is presented differently and it is combined with changes of the lyrical speaker’s attitude towards Absolute in different writing periods. The linguistic image of God is complex, because the poet rejects the Judeo-Christian tradition and also recalls it. God in the analyzed texts is omnipresent, unknowable and shapeless existence, then transforms into perceptible area, then God transforms into area that is natural element and at least he becomes a sea. In the all mentioned images God is Nameless. When the Creator becomes human like, a man searching for the God starts closer relationship with him. There are several individual descriptions which not only name the God, but also indirectly characterize him and his attitude towards creation. These descriptions evoke the tradition of naming of the God that takes its origin in the Bible. The evolution of the ways of naming and addressing the God in different writing periods of Zbigniew Jankowski’s poetry is an important element of the linguistic image of God and it also presents the system of the poet’s values.